The Role of Dendritic Cell Subsets in Recurrent Spontaneous Abortion and the Regulatory Effect of Baicalin on It - Nannan Lai; Xiaoxiao Fu; Guozhen Hei; Weiwei Song; Ran Wei; Xiaoxiao Zhu; Qiang Guo; Zhen Zhang; Chu Chu; Ke Xu; Xia Li (Journal of Immunology Research)
Recurrent spontaneous abortion (RSA) is a relevant complication of pregnancy. Aberrant dendritic cell (DC) activities and differentiation have been identified to be involved in RSA, but the underlying mechanisms remain unclear. Baicalin from Radix Scutellariae possesses a wide range of pharmacological and biological activities. However, the effect of baicalin on DC function in RSA has not been investigated. Here, we analyzed the changes of peripheral and maternal-fetal interface DC subsets and function in patients and mice with RSA, respectively. Then, we further treated RSA mice with baicalin and analyzed the therapeutic effect and underlying mechanism. We found that DCs from the peripheral blood and decidua of RSA patients and the maternal-fetal of RSA mice were all polarized to conventional DCs, whose proportion was positively correlated with the mice embryo absorption rate. Moreover, DCs from RSA patients and mice showed increased expression of HLA-DR/MHC-II, CD80, and CD86 but decreased expression of CD274 and 33D1. Importantly, baicalin could alleviate embryo resorption of RSA mice by reversing conventional DCs to plasmacytoid DCs and functional molecule expression via inhibiting the STAT5-ID2 pathway. Our research further proved that DCs play an important role in the pathogenesis of RSA and baicalin might be used for treating RSA.